Perkembangan Kerajaan Allah di Indonesia (Jurnal Pendidikan Agama dan Teologi, 2025)
This study examines the role of the church in dealing with political dynamics in Indonesia, especially in the context of colonial and post-independence history. Indonesia is a country with historical and cultural uniqueness, including in terms of religious diversity that grew amidst the dominance of colonial powers. Although Islam developed rapidly under the Christian Dutch colonialism, the spread of Christianity continued significantly, especially through Portuguese Catholic missions and non-Dutch Protestant mission organizations. The role of the church in Indonesian history shows the tension between political authority and the autonomy of religious institutions, where the church often fell victim to colonial political control but survived and developed through social, educational, and public service roles. This study highlights how the church continues to have relevance and influence in the context of modern nationality and politics, despite facing historical and structural challenges. Through a historical-critical approach, this study seeks to uncover the dynamics of the church's role in the trajectory of Indonesian politics and its contribution to building a just and plural society.